Impact of Aortic Stenosis on Myofiber Stress: Translational Application of Left Ventricle-Aortic Coupling Simulation - Wisneski, Andrew D.; Wang, Yunjie; Deuse, Tobias; Hill, Arthur C.; Pasta, Salvatore; Sack, Kevin L.; Yao, Jiang; Guccione, Julius M. (Frontiers in Physiology, 2020)
The severity of aortic stenosis (AS) has traditionally been graded by measuring hemodynamic parameters of transvalvular pressure gradient, ejection jet velocity, or estimating valve orifice area. Recent research has highlighted limitations of these criteria at effectively grading AS in presence of left ventricle (LV) dysfunction. We hypothesized that simulations coupling the aorta and LV could provide meaningful insight into myocardial biomechanical derangements that accompany AS. A realistic finite element model of the human heart with a coupled lumped-parameter circulatory system was used to simulate AS. Finite element analysis was performed with Abaqus FEA. An anisotropic hyperelastic model was assigned to LV passive properties, and a time-varying elastance function governed the LV active response. Global LV myofiber peak systolic stress (mean ± standard deviation) was 9.31 ± 10.33 kPa at baseline, 13.13 ± 10.29 kPa for moderate AS, and 16.18 ± 10.59 kPa for severe AS. Mean LV myofiber peak systolic strains were -22.40 ± 8.73 %, -22.24 ± 8.91 %, and -21.97 ± 9.18 %, respectively. Stress was significantly elevated compared to baseline for moderate (p<0.01) and severe AS (p<0.001), and when compared to each other (p<0.01). Ventricular regions that experienced the greatest systolic stress were (severe AS versus baseline) basal inferior (39.87 versus 30.02 kPa; p<0.01), mid-anteroseptal (32.29 versus 24.79 kPa; p<0.001), and apex (27.99 versus 23.52 kPa; p<0.001). This data serves as a reference to future studies that will incorporate patient-specific ventricular geometries and material parameters, aiming to correlate LV biomechanics to AS severity.